Retrospective Analysis of 12 Months Glaucoma Implant Efficacy: XEN45 and PreserFlo Microshunt - Saletta, Giulia; Alexoudis, Antonios; Gatzioufas, Zisis; Grieshaber, Matthias; Papazoglou, Anthia; Tschopp, Markus; Töteberg, Marc; Gugleta, Konstantin (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose Several new implant devices have recently been introduced to glaucoma surgery using various techniques for reducing intraocular pressure (IOP). Two implants introduced during the past couple of years, XEN45 and PreserFlo Microshunt, are both designed to control subconjunctival filtration. There are two Swiss multicenter studies that collected the data retrospectively to analyze the efficacy and safety of these two devices separately. In this study, we report the analysis of the combined data subset from the University Hospital of Basel.Subjects and Methods The XEN45 implantation technique was introduced to Basel University Hospital in 2016 and PreserFlo Microshunt in 2018. Sixty operated patients, thirty in each group, were operated on by one surgeon, clinically followed up, and their data retrospectively analyzed from medical records. Only standalone procedures, without combined phacoemulsification, were considered in this analysis; the lens status, however, was neither an inclusion nor an exclusion criterion. Further inclusion criteria were the diagnosis of open-angle glaucoma, no previous glaucoma surgery, other than laser trabeculoplasty, and complete medical records during the 12 months of follow-up. IOP reduction during a 12-month postoperative period was the primary outcome measure as well as the number of IOP reducing drugs. The number of subsequent surgical interventions and complications/adverse events are descriptively reported.Results Patient age, gender, ophthalmological diagnosis, and initial preoperative IOP were well balanced between the two groups. Postoperative IOP course was comparable between the two methods for the first 12 months. IOP measurements were taken preoperatively and then on the first postop day, week 1, month 1, and months 3, 6, and 12 for the PreserFlo Microshunt vs. XEN45 (mmHg): 23.6 vs. 24.9, 9.0 vs. 8.9, 11.4 vs. 10.6, 13.0 vs.18.3, 16.8 vs.15.1, 15.9 vs.15.0, and 15.4 vs.14.5, respectively. IOP reducing medications were also comparable between the two groups. The study showed that subsequent interventions were more frequent in the XEN45 (13) than in the PreserFlo Microshunt group (7).Conclusion Both methods demonstrate satisfactory IOP control within a 12-month postoperative period with practically no serious adverse events/complications, but with relatively high numbers of subsequent interventions (needlings), particularly in the XEN45 group.
Keywords: glaucoma; XEN45; PreserFlo